1990
DOI: 10.1007/bf00028776
|View full text |Cite
|
Sign up to set email alerts
|

Restriction fragment length polymorphism segregation analysis of the Li locus in Trifolium repens L.

Abstract: The Li locus in white clover controls the presence of cyanogenic beta-glucosidase (linamarase) activity in leaf tissue, such that plants homozygous for the 'null' allele (li) have no linamarase activity in this tissue. The isolation of a cDNA clone from linamarase mRNA is described. The cDNA clone is used to further characterise alleles of the Li locus. Northern blot analysis shows that plants homozygous for the 'null' allele (li li) produce very reduced levels of mRNA which hybridises to the cDNA. Heterozygou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…The biochemical difference between Li Li and liii plants has been used to select linamarase clones from white clover developing leaf cDNA libraries (Hughes et at., 1990). The identity of the clones was established using hybrid select translation and immunoprecipitation of the polypeptide product.…”
Section: Molecular Geneticsmentioning
confidence: 99%
See 2 more Smart Citations
“…The biochemical difference between Li Li and liii plants has been used to select linamarase clones from white clover developing leaf cDNA libraries (Hughes et at., 1990). The identity of the clones was established using hybrid select translation and immunoprecipitation of the polypeptide product.…”
Section: Molecular Geneticsmentioning
confidence: 99%
“…The cDNA clones have also been used to analyse genomic DNA using Southern blot analysis (Hughes et at., 1990). Considerable restriction fragment length polymorphism exists in white clover for genomic sequences homologous to linamarase cDNA (Fig.…”
Section: Molecular Geneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cloned segments of the conser\-ative parts of ribosomal genes hybridize to homologous regions trom many species and have been used extensi\'ely to demonstrate restriction site variation in the rDNA within and among populations (Schaal & Learn, 1988). Otherwise, probes have been specifically cloned from the genome that is to be analyzed ('homologous probes'; Keim et al, 1989: Hughes et al. 1990).…”
Section: Restriction Length Polymorphisms In Nuclear and Chloroplast Dnamentioning
confidence: 99%
“…Breeding genetics had shown that cyanogenesis in white clover depends on active alleles at two independently segregating loci. Recently, a specific molecular probe for one of these, the gene for the hvdrolvtic enzvme linamarase has heen isolated (Hughes et al 1990). Ecoiogically, cyanogenesis seems to be primarily a defence against herb ivory.…”
Section: From Marker To Charactermentioning
confidence: 99%